Ambient assisted living : 9. AAL-Kongress, Frankfurt/M, Germany, April 20-21, 2016 - Wichert, Reiner; Mand, Beate (Springer, 2017)
In this book, leading authors in the field discuss the habitats of tomorrow. These habitats will be connected through autonomous and assistive systems, turning habitats into health resorts. This book discusses how assistance technologies enable a smooth transition from comfortable health support to medical or nursing care. The contributions have been chosen and invited at the 9th AAL congress, Frankfurt.
Keywords: Assistive computer technology -- Congresses.; Ambient intelligence -- Congresses.; Self-help devices for older people -- Congresses.; Home automation -- Congresses.; Biomedical engineering -- Congresses.; elektronické knihy; electronic books